Understandings of innovation terminology for and from emerging markets: the case of frugal innovation in a cross-country comparison. (26th May 2020) - Albert, Martin; Lange, Anne; Huesig, Stefan; Mueller, Julia; Piske, Sara; Taskiran, Cagla
We assume that the meaning, definition, and characteristics of frugal innovation and the underlying understanding of frugality may vary depending on the country and its culture. Based on this assumption we explored the appearance and understanding of frugal innovation in four emerging and developing countries, which were not yet in the prime focus of frugal innovation research: South Africa, Taiwan, Thailand, and Turkey. In our one year on-site research project, we conducted 21 expert interviews and evaluated them with qualitative content analysis in a combination of inductive and deductive category development. Our empirical results were highly consistent with our initial assumption and as summarising finding, we state, that the understanding of innovation as frugal is affected by contextual influences, especially the specific country economic conditions and the cultural context. Although the main characteristics of frugal innovation resemble one another, the contextual conditions seem to determine characteristics finally.